Bifidobacteria upregulate expression of toll-like receptor negative regulators counteracting enterotoxigenic Escherichia coli mediated inflammation in bovine intestinal epitheliocytes - Murata, Kozue (2013)
We previously established a bovine intestinal epithelial cell line (BIE cells) and showed that BIE cells are useful in vitro model system for the study of interactions between pathogenic and beneficial microorganisms and bovine intestinal epithelial cells (IECs). In the present study we aimed to select potential immunomodulatory bifidobacteria that may be used to beneficially modulate the inflammatory response in bovine IECs. We also aimed to gain insight in the molecular mechanisms involved in the anti-inflammatory effect of bifidobacteria by evaluating the role of Toll-like receptor (TLR)-2 and TLR negative regulators in the regulation of proinflamatory cytokines production and MAPK, NF-κB and PI3K pathways activation in BIE cells. Five bifidobacteria strains were evaluated in this study and according to their capacity to modulate inflammatory response of BIE cells. Despite the unique effect of each strain, four common points were found when comparing the effect of the high and moderate anti-inflammatory strains: 1) Upregulation of TLR negative regulators and the intensity of that upregulation was related to the different immunomodulatory capacity of each bifidobacteria strain. 2) The balance between MAPK activation and MKP-1 upregulation affected the an- ti-inflammatory effect of bifidobacteria in BIE cells. 3) The inhibition of PI3K pathway was related to the an- ti-inflammatory effect of bifidobacteria. 4) The immunoregulatory effect of bifidobacteria in BIE cells is partially de- pendent on TLR2. This study shows that BIE cells can be used for the selection of immunoregulatory bifidobacteria and for studying the mechanisms involved in the protective activity of immunobiotics against TLR4-induced inflammatory damage. In addition, we have demonstrated that the anti-inflammatory effect of bifidobacteria was achieved by a com- plex interaction of multiple TLRs negative regulators as well as the inhibition/activation of multiple signaling pathways.